Developing Alternative Mangrove Ecosystem Management Scenarios through Economic Valuation in the Coastal Area of Jangkaran Village, Kulon Progo Regency, Indonesia - Dwike Ariestantya; Rika Harini (Universitas Gadjah Mada, 2019)
Mangrove ecosystems have multiple functions, including economic and environmental ones. For optimal benefits, mangrove ecosystem management should be well-proportioned. The purpose of this study was to determine the most appropriate scenario for managing a mangrove ecosystem alongside aquaculture ponds, by performing an economic valuation to find out the value of management with the most beneficial scenarios, both ecologically and economically. Data were collected through interviews using questionnaires, literature reviews, and institutional data. These data were then processed through economic valuations of the total economic value and cost-benefit analysis. Data were analysed spatially and descriptive-quantitatively. The total economic value of the mangrove ecosystem was USD 6.73 million. The benefit and costs of managing mangrove ecotourism were USD 3,930.74/ha/year and USD 1,701.69/ha/year, respectively, whereas the benefits and costs of managing ponds were USD 150,433.85/ha/year and USD 55,269.46/ha/year, respectively. The prioritized scenario of mangrove ecosystem management is one with an ideal proportion of mangrove and pond areas (i.e. 50:50) and the total ecological and economic benefits for a period of 25 years is USD 19.17 million.